1998
DOI: 10.1143/jjap.37.l309
|View full text |Cite
|
Sign up to set email alerts
|

High-Power, Long-Lifetime InGaN/GaN/AlGaN-Based Laser Diodes Grown on Pure GaN Substrates

Abstract: Epitaxially laterally overgrown GaN on sapphire was used to reduce the number of threading dislocations originating from the interface of the GaN epilayer with the sapphire substrate. The GaN layer above the SiO2 mask area surrounding the window, corresponding to the lateral overgrowth, was nearly free of the threading dislocations. A high density of threading dislocations was observed in the vicinity of GaN grown in the window regions. InGaN multi-quantum-well-structure laser diodes (LDs) grown on pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0

Year Published

1998
1998
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(115 citation statements)
references
References 9 publications
1
114
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] The growth of nearly TD-free GaN has been realized by the lateral epitaxial overgrowth (LEO) technique, [11][12][13][14][15][16] and the device lifetime of the cw MQW LDs has been extended up to 10,000 hours using low TD density GaN on sapphire 14 and pure GaN substrates 15 prepared by LEO technique. InGaN alloys are attracting special interest because they are adopted as active regions of ultra-violet (UV), 17 blue, 1 green, 1 and amber 18 SQW LEDs and all MQW LDs 10 and they emit bright luminescences despite of the large TD density up to 10 10 cm -3 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The growth of nearly TD-free GaN has been realized by the lateral epitaxial overgrowth (LEO) technique, [11][12][13][14][15][16] and the device lifetime of the cw MQW LDs has been extended up to 10,000 hours using low TD density GaN on sapphire 14 and pure GaN substrates 15 prepared by LEO technique. InGaN alloys are attracting special interest because they are adopted as active regions of ultra-violet (UV), 17 blue, 1 green, 1 and amber 18 SQW LEDs and all MQW LDs 10 and they emit bright luminescences despite of the large TD density up to 10 10 cm -3 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the correctness of the schema shown in Fig. 1 has been proved for GaAs ELO layers grown on GaAs [2] or GaAs-coated Si [7] substrates and for GaN ELO layers grown on GaN-coated SiC [10,13] or GaN-coated sapphire [14] substrates. The latter achievement seems to be the most spectacular one.…”
Section: Substrate Defects Filtration In the Elo Proceduresmentioning
confidence: 99%
“…The latter achievement seems to be the most spectacular one. In fact, the significant reduction of dislocation density in the GaN ELO layers has allowed for the continuous wave operation of blue GaN laser at room temperature with a lifetime in the 10 000 hours range [14].…”
Section: Substrate Defects Filtration In the Elo Proceduresmentioning
confidence: 99%
“…Then, the latest results showed that the lifetime became as long as 1000 [36] and 10 000 hours [37] under RT continuous-wave (CW) operation. Also, high power LDs were fabricated using epitaxially lateral overgrown GaN (ELOG) [38] and GaN substrates [39]. All of these light-emitting devices use an InGaN active layer instead of a GaN active layer because it is difficult to fabricate a highly efficient light-emitting device using a GaN active layer, the reason for which is still not well known.…”
Section: (153)mentioning
confidence: 99%
“…The TD increased the threshold current density of the LDs. Considering this behavior of TDs, free standing GaN substrate, which is made by growing the thick ELOG (200 µm) and, then, removing the sapphire, would be a promising substrate due to a lack of a large size of bulk GaN substrate [39,51].…”
Section: Ingan-based Violet Ldsmentioning
confidence: 99%